Associations of wheezing phenotypes in the first 6 years of life with atopy, lung function and airway responsiveness in mid-childhood. Issue 11 (4th August 2008) - Henderson, J; Granell, R; Heron, J; Sherriff, A; Simpson, A; Woodcock, A; Strachan, D P; Shaheen, S O; Sterne, J A C
Abstract : Background: Patterns of wheezing during early childhood may indicate differences in aetiology and prognosis of respiratory illnesses. Improved characterisation of wheezing phenotypes could lead to the identification of environmental influences on the development of asthma and airway diseases in predisposed individuals. Methods: Data collected on wheezing at seven time points from birth to 7 years from 6265 children in a longitudinal birth cohort (the ALSPAC study) were analysed. Latent class analysis was used to assign phenotypes based on patterns of wheezing. Measures of atopy, airway function (forced expiratory volume in 1 s (FEV1 ), mid forced expiratory flow (FEF25-75 )) and bronchial responsiveness were made at 7–9 years of age. Results: Six phenotypes were identified. The strongest associations with atopy and airway responsiveness were found for intermediate onset (18 months) wheezing (OR for atopy 8.36, 95% CI 5.2 to 13.4; mean difference in dose response to methacholine 1.76, 95% CI 1.41 to 2.12 %FEV1 per μmol, compared with infrequent/never wheeze phenotype). Late onset wheezing (after 42 months) was also associated with atopy (OR 6.6, 95% CI 4.7 to 9.4) and airway responsiveness (mean difference 1.61, 95% CI 1.37 to 1.85 %FEV1 per μmol). Transient and prolonged early wheeze were not associated with atopy but were weakly associated with increased airway responsiveness and persistent wheeze had intermediate associations with these outcomes. Conclusions: The wheezing phenotypes most strongly associated with atopy and airway responsiveness were characterised by onset after age 18 months. This has potential implications for the timing of environmental influences on the initiation of atopic wheezing in early childhood.